Direct Finite Element Simulation of the turbulent flow past a vertical axis wind turbine. (May 2019) - Nguyen, Van-Dang; Jansson, Johan; Goude, Anders; Hoffman, Johan
Abstract: There is today a significant interest in harvesting renewable energy, specifically wind energy, in offshore and urban environments. Vertical axis wind turbines get increasing attention since they are able to capture the wind from any direction. They are relatively easy to install and to transport, cheaper to build and maintain, and quite safe for humans and birds. Detailed computer simulations of the fluid dynamics of wind turbines provide an enhanced understanding of the technology and may guide design improvements. In this paper, we simulate the turbulent flow past a vertical axis wind turbine for a range of rotation angles in parked and rotating conditions. We propose the method of Direct Finite Element Simulation in a rotating ALE framework, abbreviated as DFS-ALE. The simulation results are validated against experimental data in the form of force measurements. It is found that the simulation results are stable with respect to mesh refinement and that the general shape of the variation of force measurements over the rotation angles is captured with good agreement. Highlights: An efficient DFS-ALE method to simulate the turbulent flow of a vertical axis wind turbine in parked and rotating conditions. A high-performance computing software implemented in FEniCS-HPC. Good validations against experimental data in parked and rotating conditions.